The quality of academic life and its relationship with academic passion among university students - Rasha Bassiouni Al-Desouki; Mohamed Sayed Abdellatif; Abdelfattah Issa Idris; Ahmed F. A. Mohammed (Journal of Education and Health Promotion)
BACKGROUND: At a time prioritizing the comprehensive growth and welfare of university students, grasping the profound importance of both the quality of academic life and the intricacies of academic passion emerges as crucial for educators, administrators, and policymakers. This research investigates the levels of academic life quality and academic passion among university students, aiming to uncover the intricate relationship between these dimensions. Additionally, the study explores the feasibility of predicting academic life quality based on academic passion. MATERIALS AND METHODS: A total of 454 male and female students at Prince Sattam bin Abdulaziz University participated in the research. The researchers administered scales for academic life quality and academic passion. They employed a descriptive-analytical approach, specifically the correlational predictive method, to shed light on the relationship pattern between research variables and predict relationships among them. RESULTS: The research results showed a high level of academic life quality among the research sample and a high level of academic passion (harmonious) with a low level of academic passion (obsessive). Furthermore, the research results indicated a statistically significant positive correlation between the four dimensions of academic life quality (good social relationships, enjoyable academic integration, meaningfulness, effective time management, and overall satisfaction) and harmonious academic passion. On the other hand, a statistically significant negative correlation was found between certain dimensions of academic life quality (enjoyable academic integration, meaningfulness, effective time management, and overall satisfaction) and obsessive academic passion. However, the relationship between good social relationships and obsessive academic passion was not statistically significant. The results also demonstrated the potential to predict academic life quality from passion within the research sample. CONCLUSION: In conclusion, this research contributes valuable insights into the complex dynamics between academic life quality and academic passion among university students. These results offer implications for educational practitioners and policymakers seeking to enhance the holistic well-being and academic engagement of university students. They offer valuable insights for enhancing the overall well-being and engagement of students.